Autologus peripheral stem cell transplantation in a patient with diffuse systemic sclerosis: our experience - F. Giorgetti; M.L. Minnucci; P. Santori; L. Ercoli; M. Rossi; M. Del Papa; G. Morico; P. Squadroni; A. Olivieri; R. Centurioni (PAGEPress Publications, 2004)
The diffuse form of systemic sclerosis (SSc) can often lead to a rapidly progressive course with the involvement of the visceral organs which causes a severe prognosis. The 5-years cumulative mortality is between 30 and 60%, depending on the clinic form at the onset. Until now, no drug treatment has been proved to be efficacious against the progression of the disease or the regression of the fibrosis. Recently autologous peripheral blood stem cell (PBSC) transplantation has been found to be promising. We introduce the case of a patient, male, 56 years old, who came under our observation on February 2001, suffering from a SSc with a severe multisystem involvement of lungs, skin, heart and gastrointestinal tract, and a positive antibodies anti-Scl-70. The 8 months therapy, at first with iloprost and cyclophosphamide, then with bolus of cyclophosphamide, was ineffective, with a rapid worsening of the cutaneous and pulmonary involvement. Under the patient agreement we decided to carry out an autologous PBSC transplantation. On December 2001, we obtained the PBSC mobilization after the administration of cyclophsphamide and lenograstim and the PBSC recovery with two leucoaferesis procedures. On February 2002, we gave the conditioning therapy with: thiotepa, cyclophosphamide, fludarabine, rabbit antilymphocytic globulin; then we made the infusion of PBSC. The bone marrow recovery (GN >500 and PLT >20.000) arrived at the day + 10. For three months after the transplantion we made an antibacterial, antiviral and antifungin prophylaxis with valacocyclovir, co-trimoxazole and fluconazole. The one-year follow-up has shown an essentially good response with the improving of the skin involvement and of the subjective indicators of the disease, while the pulmonary involvement don't seen modified from the high dose therapy.